TMI investigations of very low NA Yb-doped fibers and scaling to extreme stable 4.4 kW single-mode output - Beier, Franz; Mo¨ller, Friedrich; Nold, Johannes; Sattler, B.; Kuhn, Stefan; Hupel, Christian; Hein, Sigrun; Haarlammert, N.; Schreiber, Thomas; Eberhardt, Ramona; Tu¨nnermann, Andreas (Optics InfoBase Conference Papers, 2017)
We present our recent results of scaling low-NA fibers to high average power by overcoming the TMI-limitations. We obtained a record output power of 4.4kW with a higher stability and smaller bending compared to our previous result.
CRIS-Team Scopus Importer:2023-04-20